Melhoria de um kit didático de telecomunicações da Bit9 e desenvolvimento de roteiros para ensino experimental de sistemas de comunicação - MOREIRA, Gabriel dos Santos (2024)
This work presents the development of a set of experimental scripts for teaching application in practical Communication Systems laboratories, in Engineering courses. The scripts describe the experimental procedures that must be carried out using a professional telecommunications kit, manufactured by Bit9, which has been modified to enable better learning of analogue and digital communication concepts. The telecommunications kit in question has monopolar antenna arrays, automated rotation bases, transmitter and receiver based on FM modulation and digital coding. The first script describes the necessary steps for testing the transmission of monotonic signals with a variable frequency from 100Hz to 4kHz. The second script describes the steps for sending variable frequency square wave signals produced by a signal generator, and detected at the reception base using an oscilloscope. And in the third script, the steps for sending an alphabetical message in the form of coded information are described, using an Arduino microcontroller. The results demonstrate the functioning of the kit, the electrical signals involved in the communication system, and information gathered from the results of each proposed procedure. The scripts are suitable for use in a practical laboratory for teaching communication systems, and should contribute to the improvement of experimental teaching of communication systems, since they are not limited to just simulated software projects.